THE EFFECT OF MINDFULNESS ON DEPRESSION IN SINGLE MOTHERS IN BANYUMAS - Apriliyani, Ita; Triana, Noor Yunida (HEARTY, 2026)
Depression is one of the psychological disorders experienced by many single mothers due to economic pressure, parenting responsibilities, and lack of social support. This condition has an impact on quality of life and parenting skills. Mindfulness is a mindfulness-based intervention approach that has been shown to be effective in reducing symptoms of depression through emotional regulation mechanisms and increased self-acceptance. This study aims to determine the effect of mindfulness on the level of depression of single mothers in Banyumas. The research method used a quasi-experimental pre-post test design in 24 single mother intervention groups. Depression levels were measured using validated instruments. The analysis uses the Wilcoxon test. The results showed that there was a decrease in depression levels before and after the mindfulness intervention, with values Z = –2.324 and p = 0.020. A total of 12 respondents experienced a decrease in depression, 3 respondents experienced an increase, and 9 respondents remained. The conclusion of this study is that mindfulness has a significant effect in reducing the level of depression in single mothers in Banyumas. These interventions can be recommended as part of a psychosocial empowerment and support program in public health services.